Menanamkan Nilai Agama Dan Moral Dalam Pembiasaan Kegiatan Sholat Dhuha di TK Melati Aikmel, NTB (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
This study which aims to find out how important the practice of Duha prayer is in instilling religious, moral and discipline values in early childhood in accordance with the Child Development Achievement Standards (STPPA) contained in the Ministerial Regulation Education and Culture (PERMENDIKBUD) Number 137 of 2014 concerning National Early Childhood Education Standards. This activity involves children's ability to carry out religious activities by instilling religious values, morals and discipline. This research was carried out at Melati Aikmel Kindergarten with information obtained from the teaching staff at Melati Aikmel Kindergarten. The data collection methods used in this research are observation, interviews and documentation. From the results of the research that has been carried out, it is clear that instilling religious and moral values in early childhood through the habit of performing dhuha prayers in Melati Aikmel Kindergarten has an impact on the formation of children's character which can be seen from changes in children's behavior, namely: (1) children have a sense of gratitude, (2) children have a religious character, and (3) children are more disciplined with time.